2014
DOI: 10.1097/phh.0b013e31829bfa60
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between County-Level Contextual Characteristics and Use of Diabetes Care Services

Abstract: Objectives To examine the relationship between county-level measures of social determinants and use of preventive care among US adults with diagnosed diabetes. To inform future diabetes prevention strategies. Methods Data are from the Behavioral Risk Factor Surveillance System (BRFSS) 2004 and 2005 surveys, the National Diabetes Surveillance System, and the Area Resource File. Use of diabetes care services was defined by self-reported receipt of 7 preventive care services. Our study sample included 46 806 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…The characteristics of persons with diagnosed diabetes in those counties could differ from the overall county population. Although previous studies of diabetes care services found an association between persons living in socially disadvantaged counties and lower use of diabetes education among persons with diagnosed diabetes, this report limited interpretations of findings to the county level ( 9 ).…”
Section: Limitationscontrasting
confidence: 69%
See 3 more Smart Citations
“…The characteristics of persons with diagnosed diabetes in those counties could differ from the overall county population. Although previous studies of diabetes care services found an association between persons living in socially disadvantaged counties and lower use of diabetes education among persons with diagnosed diabetes, this report limited interpretations of findings to the county level ( 9 ).…”
Section: Limitationscontrasting
confidence: 69%
“…Although the study in this report included only nonmetropolitan counties, the persons in nonmetropolitan counties without a DSME program were also less educated than those in nonmetropolitan counties with at least one DSME program. Previous national studies suggest an association between lower education levels and lower use of preventive care practices ( 9 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Alicea-Planas et al (2016) identified time constraints as a major barrier, especially to health education in community health clinics serving populations with multiple needs. Furthermore, this region presented low physician density which can strain health care quality, especially regarding disease prevention and health promotion (Luo et al, 2014). Luo et al (2014) found that in areas with greater disease burdens, health education (referred to as selfmanagement education) was less likely despite the positive effects of health education on self-care behaviors previously identified.…”
Section: Discussionmentioning
confidence: 92%